Improving the Manchester Triage System for pediatric emergency care: an international multicenter study - Seiger, N (2015)
OBJECTIVE:To validate use of the Manchester triage system in paediatric emergency care. DESIGN: Prospective observational study. SETTING: Emergency departments of a university hospital and a teaching hospital in the Netherlands, 2006-7. PARTICIPANTS: 17,600 children (aged <16) visiting an emergency department over 13 months (university hospital) and seven months (teaching hospital). INTERVENTION: Nurses triaged 16,735/17,600 patients (95%) using a computerised Manchester triage system, which calculated urgency levels from the selection of discriminators embedded in flowcharts for presenting problems. Nurses over-ruled the urgency level in 1714 (10%) children, who were excluded from analysis. Complete data for the reference standard were unavailable in 1467 (9%) children leaving 13,554 patients for analysis. MAIN OUTCOME MEASURES: Urgency according to the Manchester triage system compared with a predefined and independently assessed reference standard for five urgency levels. This reference standard was based on a combination of vital signs at presentation, potentially life threatening conditions, diagnostic resources, therapeutic interventions, and follow-up. Sensitivity, specificity, and likelihood ratios for high urgency (immediate and very urgent) and 95% confidence intervals for subgroups based on age, use of flowcharts, and discriminators. RESULTS: The Manchester urgency level agreed with the reference standard in 4582 of 13,554 (34%) children; 7311 (54%) were over-triaged and 1661 (12%) under-triaged. The likelihood ratio was 3.0 (95% confidence interval 2.8 to 3.2) for high urgency and 0.5 (0.4 to 0.5) for low urgency; though the likelihood ratios were lower for those presenting with a medical problem (2.3 (2.2 to 2.5) v 12.0 (7.8 to 18.0) for trauma) and in younger children (2.4 (1.9 to 2.9) at 0-2 months [corrected] v 5.4 (4.5 to 6.5) at 8-16 years). CONCLUSIONS: The Manchester triage system has moderate validity in paediatric emergency care. It errs on the safe side, with much more over-triage than under-triage compared with an independent reference standard for urgency. Triage of patients with a medical problem or in younger children is particularly difficult.